2001
DOI: 10.3354/dao047073
|View full text |Cite
|
Sign up to set email alerts
|

Structural study of a possible neoplasia detected in Mytilus galloprovincialis collected from the Ria of Vigo (NW Spain)

Abstract: Several specimens of Mytilus galloprovincialis, collected in the Ria of Vigo over a non-consecutive 2 yr period (1993 to 1994 and 1996 to 1997), presented a possible gonadal neoplasm, entailing morphologically abnormal germinal cells distributed throughout the follicle and invading the adjacent storage tissue. In some cases, affected cells were noted in gonoducts and in haemic sinusoids. Prevalence of this anomaly in the samples was 6%, and all affected individuals were found between April and June. During the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 14 publications
0
16
1
Order By: Relevance
“…High loads of some contaminants (as lead, nickel and vanadium) in station 1 (Table 4) may results in the neoplasic disorders observed in X. securis. These tree elements have been reported as citogenics and mutagenics in M. galloprovincialis in the Ria de Vigo (Alonso et al 2001).…”
Section: Pathologymentioning
confidence: 97%
See 1 more Smart Citation
“…High loads of some contaminants (as lead, nickel and vanadium) in station 1 (Table 4) may results in the neoplasic disorders observed in X. securis. These tree elements have been reported as citogenics and mutagenics in M. galloprovincialis in the Ria de Vigo (Alonso et al 2001).…”
Section: Pathologymentioning
confidence: 97%
“…Gonadal neoplasia has been also recorded in M. galloprovincialis collected from a raft in the Ría de Vigo, with a mean prevalence of 6% (Alonso et al 2001). The neoplasia detected in X. securis is similar to that observed in a case of germinoma found in a mussel from the Ría do Burgo (Villalba 2006).…”
Section: Pathologymentioning
confidence: 99%
“…In Europe, Alonso et al (2001) reported a possible gonadal neoplasm in Mytillus galloprovincialis from Galicia, Spain. Twomey and Mulcahy (1984) diagnosed hemic neoplasms arising in the gonad of the common cockle Cerastoderma edule and subsequently suggested that this sarcoma may derive from germinal epithelium of the gonad (Twomey and Mulcahy, 1988).…”
mentioning
confidence: 98%
“…Haemocytic leukemia has been reported in Mytilus subspecies along the northwest coast of the United States (Mix 1983;Elston et al 1988;Krishnakumar et al 1999), the United Kingdom (Green and Alderman 1983), Denmark (Rasmussen 1996), Spain (Alonso et al 2001), Chile (Camplans et al 1998), Italy (Zizzo et al 1991), and southern British Columbia (Wong et al 1984;Bower 1989). Haemocytic leukemia outbreaks in Mya have been documented in Chesapeake Bay (Farley et al 1986), New Bedford Harbour (Reinisch et al 1984), Long Island Sound (Brousseau 1987), and Prince Edward Island (McGladdery et al 2001).…”
Section: Introductionmentioning
confidence: 99%